Hemodynamic changes for half cover left subclavian artery ostium during thoracic endovascular aortic repair - Li, Xiaowei; Yuan, Xiaoming; Wen, Zan; An, Minghua; Bi, Wei (Frontiers in Surgery, 2024)
Purpose Some clinicians use endografts to cover half the left subclavian artery (LSA) ostium to cure some cases with insufficient proximal landing zone (PLZ) in thoracic endovascular aortic repair (TEVAR) treatment. We used computational fluid dynamics (CFD) to study the hemodynamic changes in the LSA because they may cause acute thrombosis or arteriosclerosis. Methods The digital model of the aortic arch was established and named model A, which only included the supraarch branch of the LSA. By directly covering half of the LSA ostium, which was named as model B. All established models were imported into the Gambit grid division software for grid division and were subsequently imported into the Fluent software for hemodynamic numerical simulation and calculation to analyze the related changes in LSA hemodynamic parameters after stent implantation. Results Under the same aortic inlet flow, in model B, the local blood flow velocity of the LSA ostium increased and the whole blood flow velocity at the distal end decreased. The average wall shear stress (WSS) of the LSA was significantly decreased. Meanwhile there was an obvious turbulent flow in the LSA lumen, and the related blood flow state was disordered. Conclusion CFD research confirmed that the implantation of an endograft covering half the LSA ostium can cause obvious hemodynamic changes, which is likely to cause a long-term arteriosclerosis or acute thrombosis of the LSA, finally increasing the risk of stroke. Once this operation is performed in some specific clinical cases for simplicity and economy, it seems that we should actively antiplatelet and follow up regularly.